Écriveuses du Web : abondance et remix - Paule Mackrous (Itinéraires)
Writers of the Web refer to these women appropriating online spaces to enter the Web and then write about it. Two concepts enable the analysis of their practice: the abundance and the remix. Writing on the Web is primarily being involved in digital abundance, that is, to participate in the influx of online productions. Writers also put themselves in a state of abundance: writing to keep a creative flow and share the fruits of their mental activity with others. This type of writing often takes the form of a remix, a collage created from one or several cultural productions. It can also take the form of an identity remix, that is, a way to explore an aspect of their personality and to test new forms of writing.